Short-term Effects of Date Palm Extract (Phoenix dactylifera) on Ischemia/Reperfusion Injury Induced by Testicular Torsion/Detorsion in Rats - Jahromi, Alireza Raayat (Pharmacognosy Res, 2017)
BACKGROUND: Antioxidants are potent scavengers of free radicals and have beneficial effects on human health. OBJECTIVE: The aim of this study was to investigate the potential protective antioxidant activity of the edible portion of date fruit extract in an experimental testicular torsion/detorsion (T/D) model in rats. MATERIALS AND METHODS: To investigate the potential protective effects of date palm (DP), 30 male Spraque-Dawley rats were divided into three groups: sham-operated, T/D, and T/D + DP-treated (500 mg/kg, PO) groups. Testicular ischemia was induced via keeping the left testis under 720° clockwise torsion for 2 h (h), afterward, detorsion was performed. All rats were sacrificed 4 h after detorsion. Serum malondialdehyde (MDA) concentration, total oxidative status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and histopathological damage score were evaluated. RESULTS: Serum MDA, TOS, and OSI levels rose significantly in the T/D group. These values were lower in the T/D + DP group. TAS values decreased significantly in T/D group and rose in T/D + DP group. Severe injury was seen in the twisted testes of T/D group. In contrast, ipsilateral-twisted testicular tissue in the DP-treated group showed moderate-to-mild changes. Contralateral testicular tissue in the T/D group had a mild-to-moderate tissue injury; meanwhile, treated group revealed normal-to-mild changes. Spermatogenesis was significantly improved in DP-treated group when compared with the T/D group. CONCLUSION: The findings suggest a possible protective effect of DP against testicular oxidative damage induced by T/D; however, more detailed studies are warranted. SUMMARY: Given the presence of several phenolic compounds possessing high antioxidant activity in DP, it could potentially be used to reduce testis ischemia/reperfusion-induced damage. [Image: see text] Abbreviations Used: TAS: Total antioxidant status,TOS: Total oxidative status; OSI: Oxidative stress index; MDA: Malondialdehyde; C: Congestion; H: Hemorrhage, E: Edema; SG: Sloughed germinal cells; SA: Spermatogenesis arrest; STD: Seminiferous tubules disorganization; STA: Seminiferous tubules atrophy; G: Giant cells; T/D: Torsion/detorsion; DP: Date palm